Feasibility, safety and tolerability of the CREB-binding protein/β-catenin inhibitor OP-724 in patients with advanced primary biliary cholangitis: an investigator-initiated, open-label, non-randomised, two-centre, phase 1 study - Eiichi Ogawa; Atsushi Tanaka; Kenichi Harada; Hiroshi Yatsuhashi; Kazumoto Murata; Masamichi Kimura; Jun Imamura; Masanao Saio; Yoshihiro Ikura; Kouichi Miura; Ichiro Ieiri; Kiminori Kimura (BMJ Open Gastroenterology)
Objective This study aimed to evaluate the safety and tolerability of OP-724, a CREB-binding protein/β-catenin inhibitor, in patients with advanced primary biliary cholangitis (PBC).Design An open-label, non-randomised, phase 1 trial was conducted at two hospitals in Japan. Patients with advanced PBC classified as stage III or higher according to the Scheuer classification by liver biopsy between 4 September 2019 and 21 September 2021 were enrolled. Seven patients received intravenous OP-724 infusions at escalating dosages of 280 and 380 mg/m2/4 hours two times weekly for 12 weeks. The primary endpoint was the incidence of serious adverse events (SAEs). The secondary endpoints were the incidence of AEs and the improvement in the modified Histological Activity Index (mHAI) score.Results Seven patients (median age, 68 years) were enrolled. Of these seven patients, five completed twelve cycles of treatment, one discontinued prematurely for personal reasons in the 280 mg/m2/4 hours cohort, and one in the 380 mg/m2/4 hours cohort was withdrawn from the study due to drug-induced liver injury (grade 2). Consequently, the recommended dosage was determined to be 280 mg/m2/4 hours. SAEs did not occur. The most common AEs were abdominal discomfort (29%) and abnormal hepatic function (43%). OP-724 treatment was associated with histological improvements in the fibrosis stage (2/5 (40%)) and mHAI score (3/5 (60%)) on histological analysis.Conclusion Administration of intravenous OP-724 infusion at a dosage of 280 mg/m2/4 hours two times weekly for 12 weeks was well tolerated by patients with advanced PBC. However, further evaluation of antifibrotic effects in patients with PBC is warranted.Trial registration number NCT04047160.